Effect of Insect Larval Midgut Proteases on the Activity of Bacillus thuringiensis Cry Toxins - Fortier, Mélanie (American Society for Microbiology (ASM), 2007)
To test the possibility that proteolytic cleavage by midgut juice enzymes could enhance or inhibit the activity of Bacillus thuringiensis insecticidal toxins, once activated, the effects of different toxins on the membrane potential of the epithelial cells of isolated Manduca sexta midguts in the presence and absence of midgut juice were measured. While midgut juice had little effect on the activity of Cry1Aa, Cry1Ac, Cry1Ca, Cry1Ea, and R233A, a mutant of Cry1Aa from which one of the four salt bridges linking domains I and II of the toxin was eliminated, it greatly increased the activity of Cry1Ab. In addition, when tested in the presence of a cocktail of protease inhibitors or when boiled, midgut juice retained almost completely its capacity to enhance Cry1Ab activity, suggesting that proteases were not responsible for the stimulation. On the other hand, in the absence of midgut juice, the cocktail of protease inhibitors also enhanced the activity of Cry1Ab, suggesting that proteolytic cleavage by membrane proteases could render the toxin less effective. The lower toxicity of R233A, despite a similar in vitro pore-forming ability, compared with Cry1Aa, cannot be accounted for by an increased susceptibility to midgut proteases. Although these assays were performed under conditions approaching those found in the larval midgut, the depolarizing activities of the toxins correlated only partially with their toxicities.